2023
DOI: 10.3390/jpm13071022
|View full text |Cite
|
Sign up to set email alerts
|

Early Complication Analysis of Dynamic Intraligamentary Stabilization versus Anterior Cruciate Ligament Reconstruction

Frank Endreß,
Reinhard Hörner,
Wolfgang Hauth
et al.

Abstract: Purpose: Both dynamic intraligamentary stabilization (DIS) and reconstruction (RECO) are common treatment methods for anterior cruciate ligament (ACL) rupture. We report short term outcomes after DIS (Ligamys, Mathys, Bettlach, Switzerland) and RECO using semitendinosus tendon. We compared postoperative complications, deficits of range-of-motion (ROM), and revision rates between the two treatment options. Methods: A total of 690 patients (437 male, 253 female), after either DIS or RECO, were included. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The anterior cruciate ligament (ACL) plays an important role in the stabilization of the knee joint and the motor control mechanism of the knee [1]. ACL reconstruction (ACLR) is one of the most common orthopedic surgical procedures performed by sports physicians since ACL is one of the most common injuries suffered by athletes [2][3][4]. It has been reported that the risk of ACL injury is higher in competitive women and young athletes aged 15-25 years [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The anterior cruciate ligament (ACL) plays an important role in the stabilization of the knee joint and the motor control mechanism of the knee [1]. ACL reconstruction (ACLR) is one of the most common orthopedic surgical procedures performed by sports physicians since ACL is one of the most common injuries suffered by athletes [2][3][4]. It has been reported that the risk of ACL injury is higher in competitive women and young athletes aged 15-25 years [5,6].…”
Section: Introductionmentioning
confidence: 99%